2023
DOI: 10.1021/acs.jpclett.2c03691
|View full text |Cite
|
Sign up to set email alerts
|

Different Stepwise Growth Mechanism of AIE-Active Tetraphenylethylene-Functionalized Metal–Organic Frameworks on Au(111) and Cu(111) Surfaces

Abstract: Fabricating tetraphenylethylene (TPE)-functionalized metal−organic frameworks (MOFs) with aggregation-induced emission on surfaces and understanding the growth mechanism have not yet been pursued. Herein, MOFs constructed via the Ullmanntype reaction of a C 2 -symmetry TPE derivative (p-BrTBE) on Au(111) and Cu(111) surfaces were thoroughly investigated using scanning tunneling microscopy. On a Au(111) surface, p-BrTBE molecules formed the self-assembled pattern at 298 K. Stepwise annealing led to a progressiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…In 2023, Miao et al. 87 introduced p -bromine units into tetraphenylethylene molecule in order to construct the SMOF with the Kagome lattice on Au(111) and Cu(111) surfaces. The significant discrepancies in self-assembling nanostructures between Au and Cu surfaces were illustrated by means of STM and DFT calculations.…”
Section: Geometric Topological Structure Of Smofsmentioning
confidence: 99%
“…In 2023, Miao et al. 87 introduced p -bromine units into tetraphenylethylene molecule in order to construct the SMOF with the Kagome lattice on Au(111) and Cu(111) surfaces. The significant discrepancies in self-assembling nanostructures between Au and Cu surfaces were illustrated by means of STM and DFT calculations.…”
Section: Geometric Topological Structure Of Smofsmentioning
confidence: 99%
“…Experimental evidence has consistently demonstrated that the active intramolecular motion observed in solution becomes restricted upon aggregation or in the solid state. Various methods in experiments have been employed to restrict molecular motions, including incorporating chromophores into high-viscosity media, reducing temperature, doping them within rigid polymer matrices, or embedding them into metal–organic frameworks. These molecules typically feature both electron donor and acceptor units, indicating a strong influence of solvent polarity on the properties of the electronic states. Time-resolved fluorescence spectra indicate that the efficient occurrence of AIE arises from the elimination of ICT states due to the gradual transition from the local excited state to the ICT with increasing solvent polarity.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional MOF assembly not only reduces the degrees of freedom of this computational study but also finds application in MOF synthesis on surfaces. 30 In building a coarse-grained model, we are guided by the symmetry of the MOF, and we add a level of tunability to the simulated synthesis by introducing a modulator molecule. By simulating the MOF self-assembly via coarse-grained molecular dynamics simulations, we explore the influence of modulation on the crystallinity, resulting in the tuning of MOF properties through defect engineering.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Simulated modulator moleculesreagents used to control the assembly process and allowing for greater reversibility of MOF formation, i.e., to correct structural errors , are introduced to understand defect formation along with tuning MOF reactivity and crystalline domain size. Two-dimensional MOF assembly not only reduces the degrees of freedom of this computational study but also finds application in MOF synthesis on surfaces …”
Section: Introductionmentioning
confidence: 99%